Diseño y aplicación de un modelo de análisis y evaluación del vínculo investigación-docencia del posgrado en una universidad pública mexicana (Segunda de dos partes) - Garduño Madrigal, Felipe (CIENCIA ergo-sum, 2017)
This paper proposes a model and reports on its application as an instrument for evaluation of the degree of articulation between research and teaching in graduate studies at the UAEM. These two activities are usually the responsibility of one single person, but they are developed without the existence of a strategy which draws together the curricular aspects of the process of teaching- learning, and the participation of students and teachers lo accomplish it. Some possibilities to analyze particularities of the process are explored.